Colchicine in Patients with Chronic Coronary Disease - Nidorf, Stefan M; Fiolet, Aernoud T.L; Mosterd, Arend; Eikelboom, John W; Schut, Astrid; Opstal, Tjerk S.J; The, Salem H.K; Xu, Xiao-Fang; Ireland, Mark A; Lenderink, Timo; Latchem, Donald; Hoogslag, Pieter; et al. (The New England journal of medicine, 2020)
Patients with chronic coronary disease were randomly assigned to receive 0.5 mg of colchicine once daily or matching placebo. The incidence of the composite end point of cardiovascular death, spontaneous myocardial infarction, ischemic stroke, or ischemia-driven coronary revascularization was significantly lower with colchicine than with placebo.